(untitled) (Journal of Nobel Medical College, 2020)
Background: Sexual assault is one of the heinous and barbarous crimes and continues to plague our nation. It is present in every countries cutting across boundaries of culture, race, gender, relationship, social standing and the extremes of ages. The current study aims to analyze the incidence of sexual assault cases, their socio-demographic parameters, incidence to reporting time and relationship of the assailant with the victim and pattern of injury for evaluation of sexual assault. Materials and Methods: The medico-legal reports of 102 sexual assaults cases were retrieved and analyzed retrospectively which was examined by Department of Forensic Medicine from October 2019 to September 2020 at Dhulikhel hospital. All the data were entered in SPSS version 25 and results were ascertained. Results: Out of 102 samples, 52 female victims and 48 accused were analyzed. Two were male victims of sodomy. The mean age was 20.54±10.78 and 27.67±11.08 for victim and accused respectively, the most vulnerable being unmarried teenagers. Most of the accused and victims were familiar with each other (81.25%) and the common incident locale was victim’s own house. Genital injury was seen in 53.85% and general injury in 32.7% of the victims. Only 13.46 % victims and 12.50% of accused were brought for examination on the same day. Genital injury had significant association with age (p=0.003) and day of examination (p=0.029). Four of the victims were positive for pregnancy test. Conclusion: Hence this study aims to highlight that sexual assault is a catastrophe and there is a dire need of educating the vulnerable groups.